Pengaruh Lokasi Promosi dan Pelayanan terhahap keputusan pembelian pada Toko Lia 99 Semarang - Vingka Fitriana; Sukirman Sukirman (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to analyze the influence of location, promotion, and service on purchasing decisions at Toko Lia 99 Semarang. The background of this research is based on the increasing competition in the retail business, which requires companies to pay attention to factors that can influence consumers’ purchasing decisions. This study uses a quantitative approach with a survey method. Primary data were obtained through questionnaires distributed to 100 respondents who are customers of Toko Lia 99 Semarang. The research instrument was a questionnaire using a Likert scale. The data analysis technique used is multiple linear regression with the help of SPSS software. The results show that, partially, the location variable has a positive and significant effect on purchasing decisions. The promotion variable also has a positive and significant effect on purchasing decisions. Likewise, the service variable is proven to have a positive and significant effect on purchasing decisions. Simultaneously, location, promotion, and service have a positive and significant influence on purchasing decisions.